STRATEGI GURU DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN PADA SISWA DI MADRASAH IBTIDAIYAH KHADIJAH KECAMATAN KLOJEN KOTA MALANG - Wildania Ayu Rachmawati; Anwar Sa’dullah; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The ability to read the Qur'an is the ability students have in reading the Qur'an. With the aim to continue to hone the ability to read al-quran students until students can read al-quran well and correctly in accordance with the science of recitation. The ability of students to read the Qur'an varies and cannot be compared between one student and another student. Departing from these problems, the writer tries to solve these problems in MI Khadijah Malang by offering several solutions as contained in the thesis of the writer. This research uses a qualitative method with a case study research approach. Some qualitative data collection techniques are done through observation, interviews and also documentation. The results of the study showed that the students' ability to read the Qur'an was quite good. Second, the teacher's strategy in improving the ability to read al-quran on students using classical learning models, the use of media cards to arouse learning enthusiasm, especially students from the lower classes and the awarding and punishment. Finally, the obstacles faced by teachers in improving the ability to read the Qur'an to students are when students are not disciplined, the division of places for learning the Qur'an and the use of media that are small in size. These constraints can be an evaluation or improvement of learning in the future. Key word: Teacher Strategies, Reading, Al-Qur’an